Dysotriflorins A-M, triterpenoids from dysoxylum densiflorum - Nugroho, M.E.; Momota, T.; Sugiura, R.; Hanzawa, M.; Yajima, E.; Nagakura, Y.; Yasuda, N.; Hirasawa, Y.; Wong, C.P.; Kaneda, T.; Hadi, A.H.A.; Fukaya, H.; et al. (Elsevier, 2014)
Thirteen new triterpenoids, dysotriflorins A-M (1-13), were isolated from Dysoxylum densiflorum barks, and their structures were elucidated on the basis of NMR spectroscopic data and X-ray crystallography. Dysotriflorins A, B, and K-M (1, 2, and 11-13) were concluded to be unique 13,17-secodammarane triterpenoids, and dysotriflorins C-J (3-10) to be dammarane triterpenoids. Dysotriflorins showed in vitro cytotoxic activity against several cancer cell lines. (C) 2014 Elsevier Ltd. All rights reserved.